1998
DOI: 10.1074/jbc.273.26.16615
|View full text |Cite
|
Sign up to set email alerts
|

TorD, A Cytoplasmic Chaperone That Interacts with the Unfolded Trimethylamine N-Oxide Reductase Enzyme (TorA) in Escherichia coli

Abstract: Reduction of trimethylamine N-oxide (TMAO) in Escherichia coli involves the terminal molybdoreductase TorA, located in the periplasm, and the membrane anchored c type cytochrome TorC. In this study, the role of the TorD protein, encoded by the third gene of torCAD operon, is investigated. Construction of a mutant, in which the torD gene is interrupted, showed that the absence of TorD protein leads to a two times decrease of the final amount of TorA enzyme. However, specific activity and biochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
130
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 28 publications
3
130
0
Order By: Relevance
“…TorD was initially not expected to bind the twin-arginine signal peptide directly, however genetic experiments suggested E. coli TorD could indeed recognize the TorA signal peptide during the preexport proofreading process (10). Thus, TorD performs dual roles by assisting cofactor insertion into the TorA enzyme (10,(12)(13)(14) and facilitating Tat proofreading by recognition of the TorA twin-arginine signal peptide (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TorD was initially not expected to bind the twin-arginine signal peptide directly, however genetic experiments suggested E. coli TorD could indeed recognize the TorA signal peptide during the preexport proofreading process (10). Thus, TorD performs dual roles by assisting cofactor insertion into the TorA enzyme (10,(12)(13)(14) and facilitating Tat proofreading by recognition of the TorA twin-arginine signal peptide (10).…”
mentioning
confidence: 99%
“…TorA is the archetypal model Tat substrate, its twin-arginine signal peptide being the most heavily studied and exploited in the field. Loading of the cofactor is an essential prerequisite to TorA transport (11) and the TorD protein was originally identified as a cytoplasmic accessory protein required for efficient cofactor loading into the TorA apoenzyme (12)(13)(14). The 3D structure of a TorD homolog from Shewanella massilia showed that this family of proteins comprise two separate ␣-helical domains connected by a short hinge region (15).…”
mentioning
confidence: 99%
“…It has been suggested that GTP binding by REMP proteins themselves may play a role in the REMP/substrate maturation process (33). Accordingly, the domain-swapper dimer of TorD, showed an increase in GTP affinity following TorA ligand binding (27,117,118), and it was suggested to in fact be binding to the mature molybdopterin-guanine dinucleotide (MGD) form of Moco as a step in the cofactor insertion event (49). Recent investigation has illustrated strong cooperativity in the DmsD binding to both GTP and the RR-leader, suggesting that GTP binding at one site on DmsD alters affinity at additional binding sites (other protomers of a multimeric state of DmsD).…”
Section: Guanosine 5′-triphosphate (Gtp)mentioning
confidence: 99%
“…Twinarginine leader peptide binding is a canonical feature of REMPs, and as such, binding of DmsD to the DmsA RRleader peptide is an absolute prerequisite for DMSO reductase biogenesis (26,27). It is clear that DmsD binds the DmsA RR-leader at 1:1 stoichiometry and that the entire hydrophobic region is required for binding (46) although specificity is more difficult to define (47).…”
Section: So Dmso] (4)mentioning
confidence: 99%
See 1 more Smart Citation